2002
DOI: 10.1042/bj20020388
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of basic transcription element (BTE)-binding protein (BTEB) 3 and BTEB4, a novel Sp1-like protein, reveals a subfamily of transcriptional repressors for the BTE site of the cytochrome P4501A1 gene promoter

Abstract: The Sp1-like family of transcription factors is emerging as an integral part of the cellular machinery involved in the control of gene expression. Members of this family of proteins contain three highly homologous C-terminal zinc-finger motifs that bind GC-rich sequences found in the promoters of a diverse number of genes, such as the basic transcription element (BTE) in the promoter of the carcinogen-metabolizing cytochrome P4501A1 (CYP1A1) gene. In the present study, we report the molecular and functional ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 33 publications
0
39
0
Order By: Relevance
“…14 In fact, it is widely reported that different members of the KLF family may compete for the consensus sites of the promoter regions, perhaps due to similarity in their recognition sequences. [33][34][35][36][37] For example, KLF5 could abrogate the activating effect of KLF4 on the Klf4 promoter, whereas KLF4 could abrogate the inhibiting effect of KLF5 on the same promoter, and it was speculated that this competing effect was due to physical competition of the two proteins for binding to a cognate DNA sequence. 36 In another report, KLF9 competed with Sp1 for the BTE sequence in the cytochrome P4501A1 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…14 In fact, it is widely reported that different members of the KLF family may compete for the consensus sites of the promoter regions, perhaps due to similarity in their recognition sequences. [33][34][35][36][37] For example, KLF5 could abrogate the activating effect of KLF4 on the Klf4 promoter, whereas KLF4 could abrogate the inhibiting effect of KLF5 on the same promoter, and it was speculated that this competing effect was due to physical competition of the two proteins for binding to a cognate DNA sequence. 36 In another report, KLF9 competed with Sp1 for the BTE sequence in the cytochrome P4501A1 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the bHLH-PAS domains of the AhR/ARNT complex interact with the Sp1 zinc finger motif (Kobayashi et al, 1996). In contrast, a repressive role in the regulation of CYP1A1 was reported for the GC-box binding, Sp1-related transcription factors basic transcription element binding 3, basic transcription element binding 4, and gut-enriched Krüppel-like factor (Imataka et al, 1992;Zhang et al, 1998;Kaczynski et al, 2002). The observed up-regulation of CYP1A1 by MitA may be either due to interference with the GC-box in the AhRR enhancer region and a consequentially decreasing AhRR synthesis or to a displacement of repressive-acting Sp-like molecules from the CYP1A1 enhancer.…”
Section: Haarmann-stemmann Et Almentioning
confidence: 99%
“…Overlapping a C/EBP site, a basic transcription element (BTE) was identified. A BTE site in the promoter of the carcinogen-metabolizing CYP1A1 gene has been demonstrated to control the pulmonary specific regulation of CYP1A1 (35,36). In addition, several elements that have been implicated in regulating constitutive gene expression were also identified (Sp1 and AP2).…”
Section: Cloning and Nucleotide Sequence Of The Human Cyp2f1mentioning
confidence: 99%
“…A 1.3-kbp sequence from the CYP2B promoter was shown to drive lung-specific reporter gene expression in a transgenic mice, and it was shown that C/EBP␣ and C/EBP␦ regulate CYP2B pulmonary expression during differentiation (19). In addition, the promoter contains a BTE site that has been demonstrated in numerous studies (35,36,47) to regulate CYP1A1 transcription. The BTE site of CYP1A1 has been recognized to bind a number of transcription factors from the Sp/XKLF family of factors, which are involved in both constitutive and tissuespecific regulation (48).…”
Section: Investigation Of the Binding Specificity Of Lung Nuclear Extmentioning
confidence: 99%